Model Implementasi Kebijakan KB Pria di Kecamatan Kiarapedes Kabupaten Purwakarta - Pevi Aziastuti; Sutarto Mochtar; Abdul Rahman (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2022)
The problem that attempt to being solved in this research is the total of men who participate in the family planning program is extremely slow eventhough the government has created the policy regrading this program. Furthermopre, the purpose of this study was to reveal to what extent the birth control policy in the male approach was implemented in Kiara Pedes District and what obstacles were perceived when this program policy was executed in that district. In addition, this study also aims to formulate a policy model for the birth control policy in the male approach in Kiara Pedes District. Furthermore, the research method used is descriptive method with a qualitative approach. The data sample is obtained from experts who possessed the insight into the implementation of public policies in the birth control policy in the male approach in Kiara Pedes District. Eventually, the results of this study indicate that, whereas the male family planning policy has been implemented, there are still impediments that are sensed by the community, including the lack of information that the community has regarding this program and the community do not favors to consider concerning this program. Meanwhile, the factors that influence the implementation of this program policy include communication, human resources, family economic conditions, and self-concern. Furthermore, policymaking in this program requires to increase socialization to the public about the importance of this program for them.